Modeling of Electrowinning Process in Zinc Hydrometallurgy Based on COMSOL - Lu, Jiawei; An, Aimin; Qin, Yuwei; Wang, Qianqian (2022 8th International Conference on Control Science and Systems Engineering (ICCSSE), 2022)
This paper aims at the problem of the influence of the gas evolved from the electrode on the performance of the electrolytic cell during the electrowinning process of zinc hydrometallurgy. Based on the COMSOL Multiphysics software, a visually intuitive coupling model of the distribution of the tertiary current and the flow of bubbles in the zinc electrolysis cell is established. The effects of the gas released from the electrode on the concentration distribution of zinc ions, current efficiency and power consumption in the electrolytic cell were studied. These works provide an important basis for further improvement of the structure and operation of zinc electrolytic cells and subsequent optimization of electrolytic cell performance.